Restorative practices in the school environment following the non judicial ways of conflicts and facing school dropout cases (Emancipação, 2020)
The objective of the present research was to verify how Restorative Justice can help in school conflicts, as well as to verify the possibility of using restorative practices in face of school dropout. From this, it is concluded that the application of Restorative Justice within the school can reframe the reality of adolescents in conflict in school environment, generating responsibilities, giving voice to the real stakeholders in the resolution, avoiding that their conflicts are solved by third parties – that in some cases, do not even know the reality of that environment - and, allowing the involvement of the entire school and family community in cases that can be solved without judicial action, arousing in the student the interest in remaining in that school environment and preventing entry into crime. For the development of the work, it was necessary to use the bibliographical research technique, through which analyzes and readings of doctrines and articles on the subject addressed, as well discussion in the Group of Studies on Restorative Justice in Centro Universitário Campo Real in Guarapuava/Paraná.
Keywords: Restorative Justice; conflict resolution; school